The Relationship Between Body Image and Eating Patterns with Nutritional Status in Adolescent Women in Village II, Bakaran Village Stone Batang Kuis District - Erin Padilla Siregar; Sri Rezeki; Amelia Erawaty Siregar; Lisdayanti Simanjuntak (PT Inovasi Pratama Internasional, 2023)
The purpose of this study was to determine the relationship between body image and eating patterns with the nutritional status of female adolescents. This research is analytic descriptive in nature with a cross sectional survey approach. This research was conducted from February to June with a population of 68 and a sample of all respondents and sampling using total sampling with a research instrument, namely a questionnaire. Data management by means of editing, coding, tabulating, and data entry based on research results: the nutritional status of the majority of respondents who had abnormal nutrition 57 respondents (83.8%), the majority’s diet had an unbalanced diet 55 Respondents (80.9%) ), the body image of the majority of respondents has negative traits 51 respondents (75.0%). The results of the research on the relationship between Body Image and Nutritional Status show that the statistical test results obtained the Odd Ratio (OR) = 14.222.95% CI = 3.155 – 64.112 and the P value was 0.000 <0.05, which means that there is a significant relationship between Body Image and Nutritional Status in young women. The relationship between diet and nutritional status shows that the statistical test results obtained an odds ratio (OR) = 8.571.95% CI = 2.059 – 35.683 and a P. value of 0.004 <0.05, which means that there is a significant relationship between diet and nutritional status in adolescents daughter. For Adolescents It is necessary to improve perceptions of body image and ways to maintain weight without disrupting eating patterns. Wise in accessing information media to seek knowledge about good nutrition and more careful in capturing messages from peers if they receive information.